PENGARUH MOTIVASI EKSTRINSIK TERHADAP KINERJA PEGAWAI KANTOR PELAYANAN PAJAK (KPP) PRATAMA MAKASSAR BARAT MAKASSAR - Arfiany Arfiany (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The purpose of this research is to know the impact of extrinsic motivation on the performance of Tax Service Office (KPP) Pratama Makassar Barat in Makassar. The method used in this research is Likert Scale is used to measure attitudes, opinions and perceptions of a person or group of people about social phenomena. To know the degree of relationship between X with Y is used correlation coefficient. The result of this research is extrinsic motivation in Tax Office (KPP) Pratama Makassar Barat in Makassar is in low category seen from incentive aspect, job security, working condition, job status, social relationship and social security. Performance of employees in the office of Tax Service Office (KPP) Pratama Makassar Barat in Makassar is in the low category this is evident from the quality, quantity and timeliness. Extrinsic motivation has an effect on employee performance where the extrinsic motivation decreases, hence the performance of employees at Tax Service Office (KPP) Pratama Makassar Barat in Makassar will decrease also, proved from result of hypothesis testing of research with significant level 5% with dk = n-2